Microstructures, mechanical properties and deformation of near-rapidly solidified low-density Fe-20Mn-9Al-1.2C-xCr steels. (15th January 2020) - Zhang, Jianlei; Hu, Conghui; Zhang, Yunhu; Li, Jiehua; Song, Changjiang; Zhai, Qijie
Abstract: The effects of Cr addition on microstructures, mechanical properties and deformation behavior of near-rapidly solidified low-density Fe-20Mn-9Al-1.2C (wt. %) steel strips were investigated. It was found that Cr addition increased the volume fraction and size of δ-ferrite, and decreased the precipitation of κ-carbides in this low-density steel strip. The yield strength of the near-rapidly solidified steel strips was decreased significantly, but the ultimate tensile strength and the total elongation didn't obviously change. However, after cold rolling with 20% reduction, the yield strength and ultimate tensile strength of Cr-containing steel strips were significantly higher than that of the Cr-free steel strip. It was attributed to the fact that the decrease of κ-carbides caused by Cr addition facilitated the formation of high-density slip bands during cold rolling deformation. The ultimate tensile strength and total elongation of cold-rolled 3Cr (wt. %) steel strip were 1270 MPa and 21%, respectively. A double (Slip-band and Microband) hardening mechanism was proposed for the strain hardening behavior of the low-density steel strips, and the number of nanoscale κ-carbides played a crucial role in the strain hardening rate at the early strain stage. Graphical abstract: Image 1 Highlights: Cr addition increases δ-ferrite content and decreases nano-scale κ-carbide content in low-density Fe-20Mn-9Al-1.2C steel. The decrease of nano-scale κ-carbide promotes generation of the slip bands and increases its strain hardening rate. A double (Slip-band and Microband) hardening mechanism is proposed for strain hardening of the low-density steel strips.